2015
DOI: 10.5114/pjp.2015.54958
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among mismatch repair deficiency, CDX2 loss, p53 and E-cadherin in colon carcinoma and suitability of using a double panel of mismatch repair proteins by immunohistochemistry

Abstract: Biomarkers such as mismatch repair proteins, CDX2, p53, and E-cadherin are blamed for colon cancers, but the relationships of these biomarkers with each other and with pathological risk factors in colon carcinoma are still not clear. The aim of this study was to evaluate the association of these biomarkers with each other by using immunohistochemical staining and to compare their expression with pathological risk factors for colonic adenocarcinoma. We also aimed to study the usability of a double panel of mism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(72 reference statements)
5
11
0
1
Order By: Relevance
“…The association of RBM3 expression and proliferation assessed by Ki-67 expression was weak, while a significant negative correlation between RBM3 and tumor biomarker p53 was observed, indicating that high RBM3 expression is a favorable prognostic factor. We also found that Ki-67 and p53 were prognostic factors, but were not independent from other clinicopathological parameters in this study, which is consistent with other reports [ 13 , 31 33 ]. However, our study revealed that RBM3 is independent of prognostic factors, excluding Lauren grade.…”
Section: Discussionsupporting
confidence: 92%
“…The association of RBM3 expression and proliferation assessed by Ki-67 expression was weak, while a significant negative correlation between RBM3 and tumor biomarker p53 was observed, indicating that high RBM3 expression is a favorable prognostic factor. We also found that Ki-67 and p53 were prognostic factors, but were not independent from other clinicopathological parameters in this study, which is consistent with other reports [ 13 , 31 33 ]. However, our study revealed that RBM3 is independent of prognostic factors, excluding Lauren grade.…”
Section: Discussionsupporting
confidence: 92%
“…CDX2 is a transcription factor involved in differentiation and proliferation of intestinal epithelial cells, mainly in the distal part of the intestine. Loss of CDX2 expression was reported to be involved in progression of some sporadic CRCs [35][36][37][38][39].…”
Section:  Introductionmentioning
confidence: 99%
“…It is one of the most common cause of cancer-related death worldwide [2]. Cancer colon, as any cancer is caused by environmental and genetic factors [3]. 75% of cancer colon is sporadic and the remaining 30% has a hereditary contribution [4].…”
Section: Introductionmentioning
confidence: 99%